Coordenação e governança no Programa Territórios da Cidadania: uma análise multi-level a partir do Vale do Ribeira-SP - Fuser, Laura Rezende (2016)
Poverty in Brazil has been gradually reduced. Among the main reasons, there are public policies for universalization of rights. On the other hand, the municipalities' Human Development Index indicates scenarios of growing inequality. In other words, some regions, basically of rural character, were left behind in that process of development. In 2008, the “Territórios da Cidadania” (Territories of Citizenship) Program was launched by the federal government, under high expectations. It was proposed to develop those regions and to prioritize the arrival of ongoing federal public policies where they were most demanded. The program has shown an innovative arrangement which included dozens of ministries and other federal agencies, state governments, municipalities and collegialities to the palliative management and control of the territory. In this structure, both new and existing jurisdictions came to support the program coordination. This arrangement was classified as an example of multi-level governance, whose theory has been an efficient instrument to understand the intra- and intergovernmental relations under which the program took place. The program lasted only three years. In Vale do Ribeira Territory – SP, few community leaderships acknowledge it, although not having further information about its actions and effects. Against this background, the approach of this research aims to study the program coordination and governance structure (from Vale Territory, considered as the most local level, until the federal government), based on the hypothesis that, beyond the local contingencies in Vale do Ribeira, the layout and implementation of the Territories of Citizenship Program as they were formulated possess fundamental structural issues that hinder its goals of reducing poverty and inequality through promoting the development of the territory. Complementing the research, its specific goal was to raise the program layout and background in order to understand how the relations, predicted or not in its structure, were formulated and how they were developed, with special attention to Vale do Ribeira-SP. Generally speaking, it was concluded that the coordination and governance arrangement of the Territories of Citizenship Program failed for not having developed qualified solutions to deal with the challenges of the federalist Brazilian structure, party politics, sectorized public actions, or even the territory contingencies and specificities. The complexity of the program, the poverty problem proposed to be faced, and the territorial strategy of development charged a high cost of coordination, which was not accomplished by the proposal of centralization in the federal government with internal decentralization of the coordination. As the presidency changed in 2011, the program could not present results that were able to justify the arguments for its continuation, therefore it was paralyzed, lost its priority status, and the resources previously invested were redirected.